PET Study of Sphingosine-1-phosphate Receptor 1 Expression in Response to S. aureus Infection. (4th October 2021) - Jiang, Hao; Gu, Jiwei; Zhao, Haiyang; Joshi, Sumit; Perlmutter, Joel S.; Gropler, Robert J.; Klein, Robyn S.; Benzinger, Tammie L. S.; Tu, Zhude
Abstract : Sphingosine-1-phosphate receptor 1 (S1PR1) plays a crucial role in infectious diseases. Targeting S1PR1 provides protection against pathogens, such as influenza viruses. This study is aimed at investigating S1PR1 in response to bacterial infection by assessing S1PR1 expression in S. aureus -infected mice. A rodent local muscle bacterial infection model was developed by injecting S. aureus to the lower hind limb of Balb/c mice. The changes of S1PR1 expression in response to bacterial infection and blocking treatment were assessed using ex vivo biodistribution and in vivo positron emission tomography (PET) after intravenous injection of an S1PR1-specific radiotracer [ 18 F]TZ4877. The specificity of [ 18 F]TZ4877 was assessed using S1PR1-specific antagonist, NIBR-0213, and S1PR1-specific DsiRNA pretreated the animals. Immunohistochemical studies were performed to confirm the increase of S1PR1 expression in response to infection. Ex vivo biodistribution data showed that the uptake of [ 18 F]TZ4877 was increased 30.6%, 54.3%, 74.3%, and 115.3% in the liver, kidney, pancreas, and thymus of the infected mice, respectively, compared to that in normal control mice, indicating that S1PR1 is involved in the early immune response to bacterial infection. NIBR-0213 or S1PR1-specific DsiRNA pretreatment reduced the tissue uptake of [ 18 F]TZ4877, suggesting that uptake of [ 18 F]TZ4877 is specific. Our PET/CT study data also confirmed that infected mice have increased [ 18 F]TZ4877 uptake in several organs comparing to that in normal control mice. Particularly, compared to control mice, a 39% increase of [ 18 F]TZ4877 uptake was observed in the infected muscle of S. aureus mice, indicating that S1PR1 expression was directly involved in the inflammatory response to infection. Overall, our study suggested that S1PR1 plays an important role in the early immune response to bacterial infection. The uptake of [ 18 F]TZ4877 is tightly correlated with the S1R1 expression in response to S. aureus infection. PET with S1PR1-specific radiotracer [ 18 F]TZ4877 could provide a noninvasive tool for detecting the early S1PR1 immune response to infectious diseases.